THE ESP TEACHER AS A MATERIALS DESIGNER: A PRACTICAL EXAMPLE - Carbajosa Palmero, Natalia (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract In this paper, a number of materials from different pedagogical sources will be analysed from the point of view of their suitability for the ESP class. Teaching English for Specific Courses has, in the last few decades, become an optimal way of adapting linguistic needs to increasingly diversified professional and social demands. Consequently, ESP teachers have to become materials designers, selectors and researchers of a multiple, complex reality to be brought to equally changing teaching settings. On the other hand, these materials must observe certain rules (above all, they will comply with the requirement of relevance), and be considered within the linguistic paradigms more favourable to this type of teaching. An example of material implementation through a concrete unit is provided, together with the sequencing, activities and skills involved. Special emphasis is placed on authentic texts and sources provided by the students themselves, who turn out to be, in many cases, the best orientation for the teacher.